THE IMPLEMENTATION OF PROJECT-BASED LEARNING TO IMPROVE RECOUNT ESSAY WRITING OF THE EIGHTH GRADERS OF SMPN 1 TENGGARONG SEBERANG - Sudadi (CENDIKIA, 2019)
This study focuses on recount essay writing. However, teaching writing needs specific attention, method, materials, and strategy. To make students write a good writing, innovative teaching techniques are needed. In this study, PjBL is selected as the alternative to teaching recount essay The design of this study is classroom action research (CAR). The study was conducted at the eighth grader of SMPN 1 Tenggarong Seberang. The class consists of 30 students. The results of the research are: In the first cycle, there were 4 weaknesses found in different parts of techniques, in mechanics score, language score, vocabulary score and organization score. The weaknesses in the first and second cycles were the same, and in the third cycles all the weaknesses had been corrected. The average score of students’ mastery changed in every cycle. The average scores of students’ mastery in cycle I, II and III were increased in series 28.33%; 55.00% and 73.33%.